Bullying victimization and mental health problems of boarding adolescents in rural China: the role of self-esteem and parenting styles - Chen, Xu; Chen, Jing; Jiang, Huijuan; Zhao, Hongxia (BMC public health, 2025)
The mental health of adolescents is the key to ensure their smooth growth. This study aimed to explore the underlying mechanism between bullying victimization and boarding adolescents' mental health problems in rural China. A total of 2155 boarding adolescents from middle schools (N = 936, N = 1219, M = 13.86, SD = 0.81) participated in this survey and completed four questionnaires on bullying victimization, parenting styles, self-esteem and mental health problems. Results shown that: (1) In rural China, about one fifth of boarding adolescents were in an unhealthy mental state, and learning anxiety was the most common mental health problem reported by them; (2) Bullying victimization had a significant effect on boarding adolescents' mental health problems, and the more bullied experiences predict more serious mental health problems; (3) Self-esteem played a mediating role in bullying victimization and boarding adolescents' mental health problems, whiles parenting styles played a moderating role. Bullying victimization has been shown to decrease self-esteem, which in turn contributes to mental health problems among boarding adolescents. Low-level negative parenting styles further intensify these issues. Consequently, the education department and educators must prioritize addressing school bullying and protecting the mental health of boarding students. Most importantly, collaboration with parents is essential to foster the healthy development of these adolescents.